The determination strength of marine clay stabilised with quicklime - Ismail, Ghazali; Mohamed Jais, Ismacahyadi Bagus; Ramli, Harris; Ghani, Mohd Khairolden (UiTM Press, 2025)
Sub-grade or Soil stabilisation is a technique to increase the strength of the pavement layer by altering the chemical and mineral composition using chemical or non-chemical additives as the stabilising agents. Soil stabilisation using quicklime mixed with the existing subgrade/soil has been widely applied to the base or foundation in any construction by geotechnical engineers to improve or to develop desirable engineering properties for a particular construction. This paper investigates the effect of a chemical stabiliser, which is quicklime, on the strength of clay to act as a subgrade for the pavement layer. This current study focused on a series of laboratory tests consisting of initial tests on physical material characteristics of treated subgrade/soil and ungraded subgrade/soil. The analysis will focus on improving marine clay's strength while withstanding the load applied during the Unconfined Compressive Strength (U.C.S.) test. This paper also focuses on exploring the material characteristics of marine clay before and after being treated with quicklime.